English as a Madium of Instruction (EMI) in Higher Educational Establishments - Dziubata, Zoriana (Pedagogical Discourse, 2016)
Today, in the process of educational internationalization in Ukraine, the use of English as a medium of instruction (EMI) in higher educational establishments is up to date. This can help Ukraine integrate into the European educational system. In the article the notion of «English as a Medium of Instruction» has been considered, the actuality of implementing EMI-lectures into would-be specialists’ training in higher educational institutions has been substantiated and the major problems and difficulties connected with this process have been determined. Moreover, practical recommendations for the use of EMI in the courses offered in higher educational establishments in Ukraine have been given. The tendency to use EMI in higher educational institutions in Ukraine is relatively new, except for a couple of top universities of the country, which have already been training international students for a certain period of time and have highly qualified lecturers for that purpose. Thus, there are a lot of difficulties connected with the implementation of EMI-courses, such as: insufficient linguistic competence and English fluency of the majority of lecturers in Ukraine, lack of theoretical and methodological support of how to teach an EMI-course; inadequate possibilities for lecturers’ training in this field, students’ poor English and fear of getting bad academic performance. The ways to improve the implementation of EMI-courses into the process of would-be specialists’ training in higher educational institutions of Ukraine have been suggested. They are the following: state and institutional support in certifying the appropriate level of English for lecturers, workshops in order to help professors and assistant professors organize an effective EMI-course and other. Key words: higher educational establishment, lectures, English as a Medium of Instruction (EMI), workshop, linguistic and methodological support.